Implementasi Projek Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan Lil Alamin Berbasis Media Wayang dalam Meningkatkan Sikap Spiritual dan Sosial Siswa di MA Plus Al Muhibbin Jatirogo Tuban - farhatin, ummu (Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study aims to describe and analyze the implementation of the Pancasila Student Profile and Rahmatan Lil Alamin Student Profile (P5PPRA) Strengthening Project based on wayang media in improving students' spiritual and social attitudes at MA Plus Al Muh ibbin Jatirogo Tuban. In the context of increasingly complex education, it is important for educational institutions to integrate strong character values into their curriculum. Therefore, this study focuses on how this project not only functions as a learning tool, but also as a means to shape students' characters based on Pancasila values and Islamic teachings. The results of the study indicate that the implementation of this project can improve students' spiritual and social attitudes, which are reflected in their behavior of worship, tolerance, and cooperation. Students involved in wayang performances not only learn about art and culture, but also get the opportunity to internalize the spiritual values contained in each play they perform. In addition, this project also contributes to increasing tolerance among students. In the collaborative process of preparing the performance, students from various backgrounds learn to respect each other's differences and work together to achieve a common goal. This collaboration not only strengthens relationships between students, but also creates a more harmonious and inclusive learning environment.